USE OF INDEPENDENT WORK ON ENGLISH LANGUAGE CLASSES AS A MEANS OF IMPROVEMENT QUALITY OF KNOWLEDGE OF FUTURE SPECIALISTS - I.S. Zorenko (Academy of Cognitive and Natural Sciences, 2008)
In article problems of use of independent work of students on employment on English language in the higher school, as way of improvement of quality of knowledge are considered.